Antimalarial Activity of Globimetula oreophila Compounds: In Silico Docking Investigations on Plasmodium falciparum Protease - Dauda, Garba; Ali, Bila Hassan; Bawa, Bashar; Abdullahi, Maryam; Hamza, Asmau Nasiru; Sani, Yahaya Mohammed; Magaji, Muhammad Garba; Abdullahi, Musa Isma’il; Musa, Aliyu Muhammad; Hassan, Halimatu Sadiya (Sciences of Phytochemistry, 2025)
Malaria remains a major global health challenge due to its high morbidity and mortality, further complicated by growing antimalarial drug resistance. Natural products are being increasingly explored as potential sources of new therapies, with malarial proteases emerging as promising targets due to their essential roles in parasite development, invasion, egress, and hemoglobin degradation. This study evaluates the inhibitory potential of five compounds, quercetrin (DG1), dihydrostilbene (DG2), 4′-methoxy-isoliquiritigenin (DG3), stigmasterol (DG4), and quercetin (DG5), isolated from Globimetula oreophila leaves, using in silico docking against Plasmodium falciparum enzymes. Targets included falcipain-2 and falcipain-3 (cysteine proteases), SERA5 (hemoglobin-processing enzyme), PfDHFR-TS (bifunctional enzyme), and PfCDPK2 (kinase). Docking revealed strong binding affinities through hydrogen bonds, van der Waals forces, and hydrophobic interactions. DG4 showed a high affinity for PfDHFR (-10.3 kcal/mol), comparable to cycloguanil (-10.7 kcal/mol), while DG1 bound firmly to falcipain-2 (-7.9 kcal/mol), falcipain-3 (-7.5 kcal/mol), and PfCDPK2 (-9.0 kcal/mol). Binding to SERA5 ranged from -6.0 to -6.8 kcal/mol. These findings suggest that the tested compounds may act as inhibitors of vital P. falciparum enzymes, holding promise for the development of antimalarial drugs.